1994
DOI: 10.1182/blood.v84.6.1780.1780
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ras and formation of GAP complex during TPA-induced monocytic differentiation of HL-60 cells

Abstract: In this study, it was shown that the proportion of guanosine triphosphate (GTP)-bound active Ras increased in TPA (12-o- tetradecanoyl phorbol-13-acetate)-induced monocytic differentiation of HL-60 cells. The increase of active Ras was observed at 24 hours after TPA stimulation and attained to threefold (15%) over the proportion in nontreated HL-60 cells. Herbimycin A, an inhibitor of tyrosine kinase, prevented the activation of Ras, as well as the induction of monocytic differentiation. In parallel with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Vav is expressed specifically in hematopoietic cells and has the guanine nucleotide releasing factor activity for Ras which is regulated by tyrosine kinase (36). In our previous work, we could not find activation of Ras during RA-induced differentiation of HL-60 cells while the activation of Ras was observed accompanying TPA-induced differentiation (18). As the degree of tyrosine phosphorylation of Vav upon RA stimulation is higher than that upon TPA stimulation, Vav might have functions other than working as a guanine nucleotide releasing factor for Ras.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Vav is expressed specifically in hematopoietic cells and has the guanine nucleotide releasing factor activity for Ras which is regulated by tyrosine kinase (36). In our previous work, we could not find activation of Ras during RA-induced differentiation of HL-60 cells while the activation of Ras was observed accompanying TPA-induced differentiation (18). As the degree of tyrosine phosphorylation of Vav upon RA stimulation is higher than that upon TPA stimulation, Vav might have functions other than working as a guanine nucleotide releasing factor for Ras.…”
Section: Discussionmentioning
confidence: 62%
“…The protein-tyrosine kinases (PTKs) play crucial roles in the intracellular signal transduction for growth and differentiation of the cells (14). Recently, we reported that PTKs play essential roles in TPA-induced monocytic differentiation of HL-60 cells (15)(16)(17), and that Ras and GTPase-activating protein complex function downstream of PTKs during the differentiation (18). In addition, our previous paper described the induction of src family PTKs, lyn and fgr mRNA during RA-induced granulocytic differentiation (15).…”
mentioning
confidence: 99%
“…This has been reported by Katagiri et al . that Ras is not a driver in RA-induced differentiation in HL-60 33 . Finally, we note that the classical paradigms were typically derived in NIH3T3 cells where signal duration is a rapid transient.…”
Section: Discussionmentioning
confidence: 87%
“…A panel of 19 possible Raf interaction partners (kinases, GTPases, scaffolding proteins etc) was constructed based upon known signaling pathways. We did not consider the most likely binding partner, the small GTPase RAS, as previous studies have ruled it out for MAPK activation in HL-60 cells 25 , 33 . Total Raf was used as a bait protein for the immunoprecipitation studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ras proteins have been shown to regulate cell growth, differentiation, and apoptosis (78). For instance, during TPAinduced differentiation of hematopoietic leukemia cell lines, ras p21 is activated (79), and ras p21/ras p21-like G proteins are markedly induced (80), suggesting potential roles of ras proteins in cell differentiation.…”
Section: Discussionmentioning
confidence: 99%